Oral health indicators and sociodemographic factors in Brazil from 2008 to 2015 - Santos, Juliana Leandro dos; Ferreira, Raquel Conceição; Amorim, Leonardo de Paula; Santos, Anna Rachel Soares; Chiari, Antônio Paulo Gomes; Senna, Maria Inês Barreiros (Revista de Saúde Pública, 2021)
OBJECTIVE: To evaluate the annual variation of oral health and primary care coverage, the tooth extraction ratio, and the average of supervised toothbrushing in Brazilian municipalities according to social development and population size. METHODS: Public secondary data were analyzed. The outcomes were health service indicators (oral health coverage, primary health care coverage, tooth extraction ratio, and average of supervised tooth brushing) estimated for all Brazilian municipalities annually from 2008 to 2015. Mixed-effect multilevel regression models with random intercept and slopes were fitted with a cross-interaction term to estimate the annual percent variation according to the Municipal Human Development Index (MHDI) and population size. RESULTS: Municipalities with low MHDI presented an annual increase in oral health and primary care coverage of 2.65% and 2.23%, respectively, which was significantly higher than municipalities with medium and high MHDI. Oral health and primary care coverage were 69.26% and 35.00% lower among municipalities with a large population. Municipalities with medium and high MHDI showed an annual decrease in tooth extractions of 5.15% and 5.02%, respectively. An annual decrease was observed in the average of supervised toothbrushing of 9.81% and 4.57% in municipalities with low and medium MHDI, respectively. The tooth extraction ratio was higher among larger municipalities; the relation is inverse for supervised toothbrushing. CONCLUSIONS: The access to primary care and oral health services increased in Brazil, while a decrease occurred in mutilating treatment and provision of preventive actions, with disparities among municipalities with different MHDI levels over time.